2017
DOI: 10.1182/blood-2016-11-748053
|View full text |Cite
|
Sign up to set email alerts
|

Syk inhibitors interfere with erythrocyte membrane modification during P falciparum growth and suppress parasite egress

Abstract: Band 3 (also known as the anion exchanger, SLCA1, AE1) constitutes the major attachment site of the spectrin-based cytoskeleton to the erythrocyte's lipid bilayer and thereby contributes critically to the stability of the red cell membrane. During the intraerythrocytic stage of 's lifecycle, band 3 becomes tyrosine phosphorylated in response to oxidative stress, leading to a decrease in its affinity for the spectrin/actin cytoskeleton and causing global membrane destabilization. Because this membrane weakening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 71 publications
3
40
0
Order By: Relevance
“…During previous studies of human erythrocyte membranes, we observed that the erythrocytes possess a mechanism that is involved in the expulsion of denatured hemoglobin, requiring the activation of Syk [ 10 , 11 , 12 , 13 , 14 ]. This function could play a role in the process of asexual P. falciparum growth, as malaria parasites exert oxidative stress in erythrocytes, causing denaturation of hemoglobin, the oxidation of band 3, and its subsequent phosphorylation by Syk [ 15 , 16 ]. The protein band 3 (also known as the anion exchanger, AE1) constitutes the major attachment site of the spectrin-based cytoskeleton to the erythrocyte’s lipid bilayer, and thereby contributes critically to the stability of the red cell membrane [ 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…During previous studies of human erythrocyte membranes, we observed that the erythrocytes possess a mechanism that is involved in the expulsion of denatured hemoglobin, requiring the activation of Syk [ 10 , 11 , 12 , 13 , 14 ]. This function could play a role in the process of asexual P. falciparum growth, as malaria parasites exert oxidative stress in erythrocytes, causing denaturation of hemoglobin, the oxidation of band 3, and its subsequent phosphorylation by Syk [ 15 , 16 ]. The protein band 3 (also known as the anion exchanger, AE1) constitutes the major attachment site of the spectrin-based cytoskeleton to the erythrocyte’s lipid bilayer, and thereby contributes critically to the stability of the red cell membrane [ 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The band 3-based bridges formed by multiprotein complexes involving ankyrin and protein 4.1 (junctional complex) anchor the red cell membrane to the skeleton network (Figure 3, left panel) [19,109,110]. Studies in G6PD deficient red cells exposed in vitro to diamide, β-thalassemic erythrocytes or sickle erythrocytes undergoing in vitro deoxygenation, have had documented an over-activation of Syk bypassing the canonical cascade and targeting clustered band 3 [17,18,107,[114][115][116][117]. This favors the release of erythroid microparticles and the macrophage biting during transit of pathologic red cells in spleen microcirculation (Figure 3, right panel).…”
Section: Oxidation and Signal Transduction Pathways In Red Cell Pathomentioning
confidence: 99%
“…This favors the release of erythroid microparticles and the macrophage biting during transit of pathologic red cells in spleen microcirculation (Figure 3, right panel). Indeed, pharmacologic active Syk inhibitors such as imatinib in association with artemisinin have been shown to accelerate the clearance of malaria parasitized red cells by splenic macrophages [17,106,114,116,117]. Up to now, a clinical study on the effects of the combination imatinib-artemisinin treatment in patient with malaria is on-going in Vietnam (NCT#02614404).…”
Section: Oxidation and Signal Transduction Pathways In Red Cell Pathomentioning
confidence: 99%
“…Current high-throughput efforts are directed at both the blood and liver stages of the disease, and a recent report by Antonova-Koch et al (4) has struck me and more expert observers as promising. Another development, very surprising, is that there is considerable promise in a drug developed for a hematological malignancy, namely Gleevec, based on a revealed role for Syk kinases in creating the erythrocyte membrane band 3 protein tyrosine phosphorylation induced by the parasite that leads to a destabilization of the membrane-one of the parasite's many tricks (5). And one cannot fail to note that should this very promising new lead pan out, it would be a wonderful case of how basic research (which is how Gleevec was first envisioned) can radiate even beyond the first disease application (chronic myelogenous leukemia).…”
mentioning
confidence: 99%
“…Thoru Pederson Editor-in-Chief, The FASEB Journal doi: 10.1096/fj.190301ufm ACKNOWLEDGMENTS I thank Joseph Hoffman (Yale University) for alerting me to Panteleo et al (5).…”
mentioning
confidence: 99%